2022
DOI: 10.1136/bmj.o1526
|View full text |Cite
|
Sign up to set email alerts
|

What is the relationship between mode of birth, antibiotics, and childhood health?

Abstract: Long term impact of prophylactic antibiotic use before incision versus after cord clamping on children born by caesarean section: longitudinal study of UK electronic health records. BMJ 2022;377:e069704.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Increasing studies on the composition and diversity in fecal microbiota have been carried out in recent years [ 4 , 5 , 6 , 7 ]. Studies have shown that several factors such as host genotype, birth mode, age, use of antibiotics and dietary habits might alter the fecal microbial composition, and lead to chronic inflammation or metabolic dysfunction [ 8 , 9 ]. Additionally, the effects of the dietary factor on fecal microbial composition were dominant [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies on the composition and diversity in fecal microbiota have been carried out in recent years [ 4 , 5 , 6 , 7 ]. Studies have shown that several factors such as host genotype, birth mode, age, use of antibiotics and dietary habits might alter the fecal microbial composition, and lead to chronic inflammation or metabolic dysfunction [ 8 , 9 ]. Additionally, the effects of the dietary factor on fecal microbial composition were dominant [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%